A survey of depression and anxiety disorders in urban and rural Suriname - Raj Jadnanansing; Edwin de Beurs; Kajal Etwaroo; Matthijs Blankers; Rudi Dwarkasing; Jaap Peen; Vincent Lumsden; Robbert Bipat; Jack Dekker (BMC, 2022)
Abstract Background Suriname is a Low-middle income country consisting of diverse population groups. Epidemiological studies concerning mental disorders like depression and anxiety had not been conducted until 2015. The treatment gap for mental disorders in Low and middle-income countries (LMICs) may reach 76-80% as treatment is not always readily available. In this study, we estimate and compare the prevalence of potential cases of depression and anxiety, as well as the size of the treatment gap in a rural (Nickerie) and urban (Paramaribo) region of Suriname, a lower middle-income country. Methods Subjects were selected by a specific sampling method of the national census bureau. The Center for Epidemiological Studies-Depression (CES-D) was used to assess depression. Generalized anxiety disorder was assessed with the Generalized Anxiety Disorder 7 (GAD-7) and The Agoraphobic Cognitions Questionnaire (ACQ), the Body Sensations Questionnaire (BSQ) were used to assess Panic disorder. The treatment gap was calculated by estimating the percentage of subjects with depression or anxiety that did not seek out professional help. Results About 18% of the respondents from Nickerie and 16% from Paramaribo were at risk of depression and the established cut-off values of the instruments used indicate that about 3-4% in both regions may suffer from Generalized Anxiety Disorder. Women in both samples were most at risk of high anxiety about body sensations and maladaptive thoughts about panic. The treatment gap varies between 78 and 100% for the two disorders. Conclusions A high depression rate has been found in both areas, especially among young females. In addition, a high treatment gap is noted which insinuates that more therapeutic strategies are required to tackle depression and anxiety in Suriname.